Weaving a Song of Self - JoAnne Katzmarek (Journal of the Assembly for Expanded Perspectives on Learning, 2010)
Exploring the effectiveness of narrative as a mode for relationship building as well as a means to sustain and deliver content knowledge, this article explores the instructional settings of an undergraduate English class and an online environment for a teacher preparation course.